Hubungan Tingkat Pengetahuan Agamadengan Motivasi Merokok di SMA Al Islam 1 Surakarta - Ariono, Dwi; Probandari, Ari Natalia; Damayanti, Kusmadewi Eka (Nexus Kedokteran Komunitas, 2014)
Background:The smoking behaviour is an important issue for the whole world. Based on Riskesdas 2010, the number of smokers in Indonesia year was 34.7% which ranked the 5th in the world. Smoking behaviour usually begins during adolescence, which is preceded by motivation. In Indonesia, religion is believed to be the source of moral human behavior. This research aimed to identify correlation between the level of religion related knowledge and smoking motivation among students in SMA Al Islam 1 Surakarta. Methods:The study design was analytical observational study with the approach of cross sectional. The population was grade X and XI SMA Al Islam 1 Surakarta. By using the quota sampling, 350students were selected as study sample. The data collection used questionnaires. The data were analyzed by Spearman correlation test. Results:336 people (97.43%) had a good level of religion related knowledge and 335 people (71.77%) had a low motivation to smoking. The data identified very weak negative correlation between the level of religion related knowledge and smoking (r = 0.114 and p = 0.085). Someone who has a good level of knowledge of religion was not always followed by the smoking of low motivation. Conclusions:There is a weak negative correlation but not statistically significant between the level of religion related knowledge and motivation to smoking among students in SMA Al Islam 1 Surakarta. Keywords:adolescent, smoking, motivation, religion related knowledge Â